Compliance with EU Law in Times of Disintegration: Exploring Changes in Transposition and Enforcement in the EU Member States between 1997 and 2016. (19th February 2020) - Pircher, Brigitte; Loxbo, Karl
Abstract: This article explores whether disintegration, in the form of increased non‐compliance with EU law, has occurred in the EU Member States between 1997 and 2016. The contribution is twofold. First, we develop hypotheses to test the argument that non‐compliance with EU law increases when Member States experience growing economic constraints and political turbulence. However, the hypotheses are conclusively rejected. Second, while we demonstrate distinct differences between Member States' compliance by the end of the 1990s, our time‐series analyses demonstrate that these disparities disappeared over time. Taken together, our findings not only suggest that economic factors, government capacity, and, above all, domestic politics become gradually decoupled from the European integration process but also that cultural differences in law observance become increasingly irrelevant to explain the behaviour of governments. We conclude by arguing that the strong trend towards harmonization probably is explained by a changed culture of EU transposition and enforcement.